INITIAL EVALUATION OF TREATMENT RESULTS OF AMBLYOPIA DUE TO FARSIGHTEDNESS IN CHILDREN 36-72 MONTHS OLD AT THE VIETNAM NATIONAL EYE HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To review the clinical characteristics of amblyopia due to hyperopia in children aged 36-72 months and to evaluate the initial treatment results.Subjects and methods: Clinical descriptive study without control group on patients diagnosed with amblyopia due to hyperopia aged 36-72 months examined and treated at the Refractive Department of the Central Eye Hospital from December 2024 to December 2025.Results: 120 children (228 eyes) with amblyopia due to hyperopia. Average age 61.08 ± 9.96 months (38-72 months) 36-48 months 13.3%, 49-60 months 31.7%, 61-72 months 55.0%. In 240 eyes of 120 patients, 173 eyes (72.1%) had moderate amblyopia, 55 eyes (22.9%) had severe amblyopia. Mild hyperopia 28.3%, moderate hyperopia 38.3%, severe hyperopia 33.4%. Average visual acuity before treatment: 197.33 ± 141.1 (40-800). After 1 month of treatment, moderate amblyopia decreased to 66.2%; severe amblyopia decreased to 6.3%; non-amblyopia increased to 27.5%.Conclusion: Amblyopia due to hyperopia in the age group 36-72 months is most common in moderate amblyopia (72.1%), the degree of hyperopia is evenly distributed in all levels. After 1 month of treatment with combined methods, the number of eyes with moderate amblyopia decreased to 66.2%; severe amblyopia decreased to 6.3%; eyes without amblyopia increased to 27.5%. There were no cases of complications of decreased vision, 46 eyes (19.2%) had no improvement in vision.
Keywords: Amblyopia, hyperopia, initial results, vision.